2019
DOI: 10.1038/s41577-019-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

At the intersection of DNA damage and immune responses

Abstract: DNA damage occurs on exposure to genotoxic agents and during physiological DNA transactions. DNA double-strand breaks (DSBs) are particularly dangerous lesions that activate DNA damage response (DDR) kinases, leading to initiation of a canonical DDR (cDDR). This response includes activation of cell cycle checkpoints and engagement of pathways that repair the DNA DSBs to maintain genomic integrity. In adaptive immune cells, programmed DNA DSBs are generated at precise genomic locations during the assembly and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 107 publications
0
100
0
Order By: Relevance
“…Accordingly, at the functional level, we observed that the ROS levels were reduced after two subsequent V. splendidus challenges, suggesting that hemocytes could prevent an uncontrolled respiratory burst. Moreover, hemocytes seem to avoid cellular impairment caused by DNA damage resulting from previous oxidative stress (54), with the overexpression after the second injection of the DNA repair protein XPA (55).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, at the functional level, we observed that the ROS levels were reduced after two subsequent V. splendidus challenges, suggesting that hemocytes could prevent an uncontrolled respiratory burst. Moreover, hemocytes seem to avoid cellular impairment caused by DNA damage resulting from previous oxidative stress (54), with the overexpression after the second injection of the DNA repair protein XPA (55).…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage arises more frequently when exposed to genotoxic therapies such as chemotherapies [60]. Among all forms of damage, the double-stranded breaks (DSBs) of DNA strains are the severest type [61]. These damages can be rescued by two basic DNA DSB repair ways: homologous recombination (HR) and nonhomologous end joining (NHEJ) [62][63][64].…”
Section: Cgas and Nuclear Dna Cgas Interacting With Endogenous Dna Inmentioning
confidence: 99%
“…We observed numerous transition mutations on the proviral plus strand, which is not typical of mA3 (2325). In contrast, an Apobec family member, activation-induced cytidine deaminase (AID), is known to cause hypermutations on both strands of immunoglobulin genes during B-cell differentiation (26, 27). Differences in MMTV proviral load and most proviral mutations were eliminated in AID-deficient ( Aicda −/− ) mice lacking murine AID (mAID) expression.…”
Section: Introductionmentioning
confidence: 99%